Pediatric Care According to Vagbhata: An Overview of Kaumarbhritya Principles - , Nazneen; Kumar, Ram (International Research Journal of Ayurveda & Yoga, 2024)
Ashtanga Hridaya and Ashtanga Sangrah are respected texts in ancient Indian medicine. Kaumarbhritya one of the eight branches of Ayurveda specializes in the health care of infants and children, encompassing their ailments and treatments. While the primary source for this area is the Kashyap Samhita, it is only partially accessible. Therefore, researchers often turn to other significant texts for comprehensive insights. As part of the Brihat Trayi, Ashtanga Hridaya and Ashtanga Sangrah provide a valuable resource for this knowledge. This article reviews the content on Kaumarbhritya presented in Ashtanga Hridaya and Ashtanga Sangrah. The review reveals that these texts thoroughly address the concepts of Balrog, the diseases affecting children, and their effective treatments, fulfilling the needs of students, researchers, and practitioners alike